The Police are Indecisive: Online Gambling is Rising. Facts about the Eradication of Online Gambling in the Field - Hasibuan, Edi Saputra (International Journal Labs, 2023)
Gambling, a widespread practice in society, often lures individuals with the promise of accumulating wealth from their investments. As technology advances, gambling has found a new frontier online, offering convenience to both operators and participants who can easily access it through mobile phones or computers. However, from a normative standpoint, online gambling is banned and classified as a criminal activity in Indonesia. Online gambling operators exhibit remarkable cunning in their endeavors, employing a variety of websites and enticing promotions that challenge law enforcement agencies, particularly the police, in their efforts to combat it. This study aims to elucidate the legal status of online gambling in Indonesia and shed light on the role of the police in enforcing laws related to online gambling cases. It delves into the complexities of regulating this digital vice within the framework of Indonesian law, taking into account the challenges posed by the ever-evolving online gambling landscape. Gambling continues to captivate the public's interest as a means of wealth accumulation, the online variant presents unique challenges to law enforcement. This research endeavors to explore the legal intricacies and the police's role in addressing the issue, striving for a more comprehensive understanding of the situation.